Pengaruh Model Pembelajaran Kooperatif Pair Check Terhadap Hasil Belajar Mata Pelajaran Pendidikan Agama Islam - Azri By Lahadi; Wirdati Wirdati (Prodi Pendidikan Keagamaan Islam, 2022)
Islamic religious education plays an important role in building a generation of noble character. But in fact, student learning outcomes in PAI subjects are still low. So it is necessary to use appropriate and good learning models by teachers in the learning process at school. This study aims to see the effect of the Cooperative Learning type Pair Check on learning outcomes in PAI subjects in class VIII of SMP Pembangunan Labaratorium UNP. The sampling technique in this study used purposive sampling. The data collection method in this study used a student learning outcome test. The data in this study were analyzed using the independent sample T-test. The results of hypothesis testing show that T-count = 2.523 > T-table = 2.006, so it can be stated that there is a significant influence between the Pair Check Cooperative Learning Model on student learning outcomes in PAI subjects.